2002
DOI: 10.1002/jmv.2156
|View full text |Cite
|
Sign up to set email alerts
|

Primary human herpesvirus‐6 associated with an afebrile seizure in a 3‐week‐old infant

Abstract: We describe a 3-week-old male infant with an afebrile seizure in whom serologic and polymerase chain reaction (PCR) findings support concomitant primary human herpesvirus 6 (HHV-6) infection. Although HHV-6 infection has been associated with first-time febrile seizures and encephalitis in both immunocompetent and immunocompromised hosts, it has not been associated previously with afebrile seizures in healthy infants. This report provides additional evidence of the neuropathogenic potential of HHV-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The occurrence of encephalitis and febrile or afebrile seizures as complications of primary infection has been described previously (41,43), suggesting that HHV-6 has neuropathogenic potential. In addition, HHV-6 has also been demonstrated to be the causative agent of encephalitis in adult immunosuppressed patients such as bone marrow transplant recipients (40).…”
mentioning
confidence: 71%
“…The occurrence of encephalitis and febrile or afebrile seizures as complications of primary infection has been described previously (41,43), suggesting that HHV-6 has neuropathogenic potential. In addition, HHV-6 has also been demonstrated to be the causative agent of encephalitis in adult immunosuppressed patients such as bone marrow transplant recipients (40).…”
mentioning
confidence: 71%
“…Febrile seizures were reported in approximately 10% of children with primary HHV-6 infection, representing 10 to 20% of febrile seizure cases in children under 2 years old (22,29,154,218,426 (185,196,202,278,378,445). One case report describing an infant with afebrile convulsions due to primary infection with HHV-6B demonstrated that HHV-6 infection can have a direct effect on the brain, causing convulsions in the absence of fever (459). HHV-6 DNA has been detected in cerebrospinal fluid (CSF) of children with convulsions during primary infection or reactivation (218,378).…”
Section: Clinical Manifestations Of Hhv-6 Infectionmentioning
confidence: 99%
“…The role of HHV-6 in neurological disease is poorly understood. Neurological complications such as febrile and afebrile seizures, encephalitis, and meningitis sometimes occur after primary HHV-6 infection Hall et al, 1994;Jones et al, 1994;Suga et al, 1993;Yanagihara et al, 1995;Zerr et al, 2002). Reactivation of HHV-6 in adults is believed to be responsible for encephalitis in immunocompromized hosts such as bone marrow transplant, organ transplant, and stem cell recipients (Drobyski et al, 1994;Wainwright et al, 2001;Zerr et al, 2001).…”
Section: Introductionmentioning
confidence: 99%